Patients as partners in health research: A scoping review. (21st June 2021) - McCarron, Tamara L.; Clement, Fiona; Rasiah, Jananee; Moran, Chelsea; Moffat, Karen; Gonzalez, Andrea; Wasylak, Tracy; Santana, Maria
Abstract: Background: The role of patient involvement in health research has evolved over the past decade. Despite efforts to engage patients as partners, the role is not well understood. We undertook this review to understand the engagement practices of patients who assume roles as partners in health research. Methods: Using a recognized methodological approach, two academic databases (MEDLINE and EMBASE) and grey literature sources were searched. Findings were organized into one of the three higher levels of engagement, described by the Patient and Researcher Engagement framework developed by Manafo. We examined and quantified the supportive strategies used during involvement, used thematic analysis as described by Braun and Clarke and themed the purpose of engagement, and categorized the reported outcomes according to the CIHR Engagement Framework. Results: Out of 6621 records, 119 sources were included in the review. Thematic analysis of the purpose of engagement revealed five themes: documenting and advancing PPI, relevance of research, co‐building, capacity building and impact on research. Improved research design was the most common reported outcome and the most common role for patient partners was as members of the research team, and the most commonly used strategy to support involvement was by meetings. Conclusion: The evidence collected during this review advanced our understanding of the engagement of patients as research partners. As patient involvement becomes more mainstream, this knowledge will aid researchers and policy‐makers in the development of approaches and tools to support engagement. Patient/User Involvement: Patients led and conducted the grey literature search, including the synthesis and interpretation of the findings.